Extrachromosomal Circular DNA (eccDNA): From Chaos to Function - Zuo, Shanru; Yi, Yihu; Wang, Chen; Li, Xueguang; Zhou, Mingqing; Peng, Qiyao; Zhou, Junhua; Yang, Yide; He, Quanyuan (Frontiers in Cell and Developmental Biology, 2022)
Extrachromosomal circular DNA (eccDNA) is a type of double-stranded circular DNA that derived and free from chromosomes. It has a strong heterogeneity in sequence, length, and origin and has been identified in both normal and cancer cells. Although many studies suggested its potential roles in various physiological and pathological procedures including aging, telomere and rDNA maintenance, drug resistance and tumorigenesis, the functional relevance of eccDNA remains to be elucidated. Recently, due to technological advancements, accumulated evidence highlighted that eccDNA plays an important role in cancers by regulating the expression of oncogenes, chromosome accessibility, genome replication, immune response and cellular communications. Here we review the features, biogenesis, physiological functions, potential functions in cancer, and research methods of eccDNAs with a focus on some open problems in the field and provide a perspective on how eccDNAs evolve specific functions out of the chaos in cells.